2009
DOI: 10.1016/j.bandc.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of visuospatial attention across face regions varies with emotional prosody

Abstract: It is well-established that linguistic processing is primarily a left-hemisphere activity, while emotional prosody processing is lateralized to the right hemisphere. Does attention, directed at different regions of the talker's face, reflect this pattern of lateralization? We investigated visuospatial attention across a talker's face with a dual-task paradigm, using dot detection and language comprehension measures. A static image of a talker was shown while participants listened to speeches spoken in two pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
2
9
0
1
Order By: Relevance
“…Our results using speeches containing neutral prosody showed greater attention was distributed on the right side of the talking face image (right visual field), compared to the left side. In addition to the right-side-of-face-image effect, we found that greater attention was paid to the mouth than the eye area (Thompson & Malloy, 2004; Thompson, et al 2004; Thompson et al, 2009). …”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Our results using speeches containing neutral prosody showed greater attention was distributed on the right side of the talking face image (right visual field), compared to the left side. In addition to the right-side-of-face-image effect, we found that greater attention was paid to the mouth than the eye area (Thompson & Malloy, 2004; Thompson, et al 2004; Thompson et al, 2009). …”
mentioning
confidence: 72%
“…The design used was a 2 (Noise Distraction: No, High) X 4 (Light Position: Right, Mouth, Left, Eyes) mixed design, with noise distraction between-subjects and light position within-subjects. The semantic content of speeches used in the present study was exactly the same as was previously used in a non-interactive video task paradigm (Thompson et al, 2009), however, a different female talker gave the speeches. Across studies, talkers were young adult females of Hispanic ethnic origin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations